2000
DOI: 10.1099/0022-1317-49-3-217
|View full text |Cite
|
Sign up to set email alerts
|

Binding of von Willebrand factor by coagulase-negative staphylococci

Abstract: Coagulase-negative staphylococci (CNS) are the most common infectious microorganisms isolated from prosthetic devices. To determine whether von Willebrand factor (vWF) acts as an adhesin in bacterial recognition, bacterial binding of recombinant vWF (rvWF) was studied. Eleven CNS strains, belonging to S. epidermidis, S. haemolyticus and S. hominis species, bound soluble rvWF, but to a lesser extent than S. aureus. S. epidermidis strain H2-W bound 125 I-labelled rvWF in a dose-dependent manner. The binding coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Blocking of the A1 domain with heparin revealed a 6-fold reduction of the VWF-mediated adhesion of S aureus to the endothelium ( Figure 6A). In agreement with our data, Li et al 38 previously showed a heparin-dependent reduction of bacterial binding to VWF. We confirmed the impact of the A1 domain by a reduced adherence of S aureus to functionalized surfaces coated with recombinant VWF lacking the A1 domain.…”
Section: Discussionsupporting
confidence: 83%
“…Blocking of the A1 domain with heparin revealed a 6-fold reduction of the VWF-mediated adhesion of S aureus to the endothelium ( Figure 6A). In agreement with our data, Li et al 38 previously showed a heparin-dependent reduction of bacterial binding to VWF. We confirmed the impact of the A1 domain by a reduced adherence of S aureus to functionalized surfaces coated with recombinant VWF lacking the A1 domain.…”
Section: Discussionsupporting
confidence: 83%
“…This ®nding is consistent with the previous observation that the binding of rvWF and TSP is mediated through similar cell surface structures in both CNS and S. aureus, and suggests that the inhibitory effect of rvWF may be the result of competition for the same surface receptor [9]. Glycoproteins including Clu, Vn, Tf and IgG did not inhibit binding of TSP by either S. epidermidis J9P or S. aureus Cowan 1, indicating that the binding molecules on the bacteria for TSP are not identical to those for these glycoproteins [4,8,24].…”
Section: Discussionsupporting
confidence: 81%
“…Bacteria were incubated with proteinase K 40 ìg, trypsin 100 ìg, chymotrypsin 100 ìg or 100 mM sodium periodate, as described previously [9,27]. Suspensions of bacterial cells were heated at 1008C for 30 min and rapidly ice-cooled.…”
Section: Protease Heat and Periodate Treatmentmentioning
confidence: 99%
See 2 more Smart Citations